Local impedance guides catheter ablation in patients with ventricular tachycardia. (25th November 2019) - Münkler, Paula; Gunawardene, Melanie A.; Jungen, Christiane; Klatt, Niklas; Schwarzl, Jana M.; Akbulak, Ruken Ö.; Dinshaw, Leon; Hartmann, Jens; Jularic, Mario; Kahle, Ann‐Kathrin; Riedel, René; Merbold, Lydia; et al.
Abstract: Aims: Catheter contact and local tissue characteristics are relevant information for successful radiofrequency current (RFC)‐ablation. Local impedance (LI) has been shown to reflect tissue characteristics and lesion formation during RFC‐ablation. Using a novel ablation catheter incorporating three mini‐electrodes, we investigated LI in relation to generator impedance (GI) in patients with ventricular tachycardia (VT) and its applicability as an indicator of effective RFC‐ablation. Methods and Results: Baseline impedance, Δimpedance during ablation and drop rate (Δimpedance/time) were analyzed for 625 RFC‐applications in 28 patients with recurrent VT undergoing RFC‐ablation. LI was lower in scarred (87.0 Ω [79.0‐95.0]) compared to healthy myocardium (97.5 Ω ([82.75‐111.50]; P = .03) while GI did not differ between scarred and healthy myocardium. ΔLI was higher (18 Ω [9.4‐26.0]) for VT‐terminating as compared to non‐terminating RFC‐ablation (ΔLI 13 Ω [8.85‐18.0]; P = .03), but did not differ for ΔGI between terminating vs nonterminating RFC‐ablation. Correspondingly, LI drop rate was higher for RFC‐ablation terminating the VT compared with RFC‐ablation not terminating the VT (0.63 Ω/s [0.52‐0.76] vs 0.32 Ω [0.20‐0.58]; P = .008) while there was no difference for GI drop rate. ΔLI was higher in patients with nonischemic cardiomyopathy vs patients with ischemic cardiomyopathy (16 Ω [11.0‐20.0] vs 11.0 Ω [7.85‐17.00]; P = .003). Conclusion: Our findings suggest that LI is a sensitive parameter to guide RFC‐ablation in patients with VT. LI indicates differences in tissue characteristics and generally is higher in patients with nonischemic cardiomyopathy. Hence, the etiology of the underlying cardiomyopathy needs to be considered when adopting LI for monitoring catheter ablation of VT.